2019
DOI: 10.1029/2019ja026539
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Magnetic Reconnection With a Spatially Confined X‐Line Extent: Implications for Dipolarizing Flux Bundles and the Dawn‐Dusk Asymmetry

Abstract: Using 3-D particle-in-cell simulations, we study magnetic reconnection with the X-line being spatially confined in the current direction. We include thick current layers to prevent reconnection at two ends of a thin current sheet that has a thickness on an ion inertial (d i ) scale. The reconnection rate and outflow speed drop significantly when the extent of the thin current sheet in the current direction is ≲ O(10d i ). When the thin current sheet extent is long enough, we find that it consists of two distin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(99 citation statements)
references
References 65 publications
11
88
0
Order By: Relevance
“…These simulations suggest that Mercury's magnetotail reconnection sites slightly prefer the duskside (Figure ) when the dawnside current sheet is significantly thicker than the duskside (Figures a and b) under a moderate IMF driver (MHD‐EPIC‐A), and the reconnection sites prefer the dawnside (Figure ) when the dawnside current sheet is almost as thin as the duskside (Figures c and d) under a strong driver (MHD‐EPIC‐B). The results of MHD‐EPIC‐B simulation are consistent with what Liu et al () found in 3‐D box PIC simulations. They found that there is a reconnection “suppression region” on the ion drifting side (the duskside in our simulations) of a thin current sheet, so that the magnetic reconnection prefers the electron‐drifting side.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These simulations suggest that Mercury's magnetotail reconnection sites slightly prefer the duskside (Figure ) when the dawnside current sheet is significantly thicker than the duskside (Figures a and b) under a moderate IMF driver (MHD‐EPIC‐A), and the reconnection sites prefer the dawnside (Figure ) when the dawnside current sheet is almost as thin as the duskside (Figures c and d) under a strong driver (MHD‐EPIC‐B). The results of MHD‐EPIC‐B simulation are consistent with what Liu et al () found in 3‐D box PIC simulations. They found that there is a reconnection “suppression region” on the ion drifting side (the duskside in our simulations) of a thin current sheet, so that the magnetic reconnection prefers the electron‐drifting side.…”
Section: Discussionsupporting
confidence: 89%
“…The X-lines estimated from the tailward jets (Figurs 11 and 8) are more than 1 R M wide in the cross-tail direction initially. As soon as the MHD-EPIC simulation starts, the duskside X-lines start to shrink (solid red lines in Figures 11 and 12), so that almost all the reconnection sites are in the dawn sector at t = 30 s. The shrinkage of the X lines may be related to the reconnection suppression region discussed by Liu et al (2019).…”
Section: Discussionmentioning
confidence: 95%
“…When the CS thickness is twice di, the X‐line even appears to be simply drifting, without clearly extending (Shay et al, ). Recent work (Liu et al, ) indicates that a localized X‐line can be well confined between a thick ambient CS of 8 di. The above mentioned studies use a reduced mass ratio of <100.…”
Section: Discussionmentioning
confidence: 99%
“…It is a primary driver of space weather surrounding the Earth. While two‐dimensional (2‐D) models have been widely used to describe the essential aspects of reconnection (Birn et al, ), the three‐dimensional (3‐D) dynamics represents a frontier of current reconnection research (e.g., Daughton et al, ; Janvier, ; Liu et al, , ; Nakamura et al, ; Price et al, ). In this work, we focus on the evolution of the extension of a localized reconnection X‐line in the out‐of‐plane direction.…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure and processes occurring in Mercury's magnetotail are known to be qualitatively similar to that of Earth's, they are different in spatial and temporal scale (e.g., Gershman et al, 2014;Poh et al, 2017b;Raines et al, 2011;Sun et al, 2015). Recent simulation studies (Chen et al, 2019;Liu et al, 2019) suggest that kinetic-scale dynamics and instabilities dominate in Mercury's small magnetotail (~10 d i wide, where d i is the ion inertial length), thereby explaining the observed asymmetric structure and occurrence of processes in the tail.…”
Section: Introductionmentioning
confidence: 99%